Pengaruh enzim bromelin dosis berbeda tehadap pertumbuhan dan efisiensi pemanfaatan pakan ikan Nila (Oreochromis niloticus) - Fajar Andini; Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
The ability of fish to digest food is highly dependent on the completeness of the digestive organs and the availability of digestive enzymes and as long as the feed is in the fish's intestines, the nutrients are digested by various enzymes into a form that can be absorbed by the intestinal wall and enter the fish circulatory system. Therefore, it is necessary to find alternative solutions, one of which is the addition of enzymes to optimize the digestion and absorption of feed, high digestibility will have an impact on the high efficiency of feed utilization. This study aims to determine the effect of the bromelin enzyme feed on the growth and efficiency of feed utilization and to determine how many bromelin doses can increase the growth and feed efficiency of tilapia (Oreochromis niloticus). The results of this study are expected to provide an overview of the appropriate dose of addition of bromelin enzymes in commercial feed used to increase the growth of tilapia. This study used a completely randomized design (RAL) consisting of 4 treatments (A, B, C, and D) and 3 replications (1, 2, and 3), treatment A used bromelin enzymes with a dose of 5 gr/kg of feed, treatment B used the bromelin enzyme at a dose of 10 g/kg of feed, treatment C used the bromelin enzyme at a dose of 15 g / kg of feed and treatment D as a control (without the addition of bromelin enzymes). Feeding with the addition of bromelin enzymes in tilapia feed shows that feeding containing bromelin enzymes has a very significant effect on growth in absolute weight (.001), absolute length (.000), efficiency of feed utilization (EPP) (.001), but had no significant effect on feed conversion value (FCR) (.064) and survival(0.571) Keywords : Tilapia(Oreochromis niloticus), Bromelin enzyme, growth, feed efficiency.